Culturally Relevant Resources List - Lisa Guion; Samantha Chattaraj; Stephanie Sullivan Lytle; Gae Broadwater; H. Wallace Goddard (EDIS)
A culturally relevant resource list is a critical link in connecting Children, Youth and Families at Risk (CYFAR) Extension professionals and paraprofessionals (educators) with culturally relevant resources to educate diverse audiences in various subject areas. This is why CYFAR educators from across the nation requested such a list be developed when filling out the CYFERnet environmental scan and needs assessment surveys. The Diversity Project Team designed the following resource list in response to the needs expressed by CYFAR educators by searching extensively to identify some examples of culturally relevant resources that support and strengthen CYFAR programming. The resources were reviewed by team members, county faculty and/or state specialists. All resources came from credible sources in an attempt to further ensure the accuracy of subject content. This document is PE069, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, University of Florida, UF/IFAS, Gainesville, FL 32611: First published: September 2003.